2015
DOI: 10.1088/0029-5515/55/6/063013
|View full text |Cite
|
Sign up to set email alerts
|

The negative triangularity tokamak: stability limits and prospects as a fusion energy system

Abstract: The paper discusses edge stability, beta limits and power handling issues for negative triangularity tokamaks. The edge MHD stability is the most crucial item for the power handling. For the case of negative triangularity the edge stability picture is quite different from that for conventional positive triangularity tokamaks: the 2nd stability access is closed for localized Mercier/ballooning modes due to the absence of magnetic well, and nearly internal kink modes set the pedestal height limit weakly sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
107
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(119 citation statements)
references
References 31 publications
11
107
0
1
Order By: Relevance
“…This paper reports on experimental studies aiming at (i) understanding the effect of plasma shaping and reversing toroidal magnetic field polarity to support further theoretical work, e.g. the importance of drifts and turbulence on scrape-off layer heat flux and (ii) scaling the effect of negative triangularity for accessing the reactor design with negative triangularity [5,6,7]. The Tokamakà Configuration Variable (TCV) [8,9] is able to achieve a large variety of plasma shapes due to 16 independently powered poloidal field coils and an open vessel geometry.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…This paper reports on experimental studies aiming at (i) understanding the effect of plasma shaping and reversing toroidal magnetic field polarity to support further theoretical work, e.g. the importance of drifts and turbulence on scrape-off layer heat flux and (ii) scaling the effect of negative triangularity for accessing the reactor design with negative triangularity [5,6,7]. The Tokamakà Configuration Variable (TCV) [8,9] is able to achieve a large variety of plasma shapes due to 16 independently powered poloidal field coils and an open vessel geometry.…”
Section: Introductionmentioning
confidence: 90%
“…A triangularity dependence of the power fall-off length λ q in combination with reversed toroidal field has been observed in ASDEX Upgrade [16]. Negative triangularity has been investigated in TCV [17,18] and reactor studies [5,6,7]. Such investigations showed increased energy confinement with negative triangularity in low [19] and medium [20] density plasmas, explained by a reduction of turbulent transport [21].…”
Section: Introductionmentioning
confidence: 99%
“…Historically the −δ shape has been considered to have low β stability limits to ballooning modes due to the fraction of plasma volume with bad field line curvature. However, a recent study of the −δ shape found a limit β N > 3.0 is possible [13]. Moreover, a study of growth rates of n = 1 kink modes using the GATO code [14], employing scaled DIII-D experimental profiles, found a beta limit β N = 3.1, so the notion of low β limits in this shape is not borne out in modeling or experiment.…”
mentioning
confidence: 99%
“…This risk poses a serious question mark on the suitability of H-mode as a reactor scenario, since a reliability of 100% would be required to any chosen ELM mitigation or suppression method, a challenging engineering target to meet (even disregarding other drawbacks all active ELM mitigation or suppression techniques might have concerning the plasma performance). For this reason, a plasma scenario which is naturally ELM-free, as for example the QH-mode [37], the I-mode [38], or even negative triangularity [39,40,41] would be extremely beneficial for a machine like EU-DEMO, whose mission includes stringent availability requirements -to a much higher extent than ITER, which is still an experiment.…”
Section: Elm-free Regimesmentioning
confidence: 99%